The production is left-recursive if the leftmost symbol on the right side is the
same as the non terminal on the left side. For example,

expr
→
expr + term.

If one were to code this production in a recursive-descent parser, the parser would go in an infinite loop.

diagram

We can eliminate the left-recursion by introducing new nonterminals and new productions rules.

For example, the left-recursive grammar is:

E → E + T | T

E → T * F | F

F → (E) | id.

We can redefine E and T without left-recursion as:

E → TE`

E`→ + TE` |ET → FT`

T → * FT` |EF → (E) | id

Getting rid of such immediate left recursion is not enough. One must get rid
of indirect left recursion too, where two or more nonterminals are mutually
left-recursive.